A quantitative and mechanistic model for the coupling between chemistry and clay hydration. (15th August 2020) - Marty, Nicolas C.M.; Grangeon, Sylvain; Lassin, Arnault; Madé, Benoit; Blanc, Philippe; Lanson, Bruno
Highlights: Smectite water vapor isotherms modelled using an ion exchange formalism. Model accounting for the interlayer composition and relative humidity. Model accounting for the charge location. Hydration and stability of the clay layer processed independently. Abstract: It is proposed here to describe smectite water vapor desorption isotherms using an exchange formalism that quantitatively accounts for the different hydration states and thus different water contents. This approach makes it possible to reproduce both desorption isotherms and relative proportions of the different hydration states as determined by X-ray diffraction. The method is numerically robust and easy to implement in most reactive transport codes. The formalism is satisfactory from a phenomenological point of view and accounts for the influence of external parameters such as interlayer cation composition and solution cation composition and salinity on clay hydration. Furthermore, in contrast to most solid solution models, this approach focuses on the clay reactivity according to the charge and type of interlayer cation rather than on its solubility and therefore does not require the overall thermodynamic properties of the clay. In addition, such an explicit distinction of the hydration/cation exchange processes from the thermodynamic stability of smectite 2:1 layer allows the use of kinetics driving slow dissolution/precipitation rates if the number of exchange sites is related to the amount of clay minerals.